QUALITATIVE ANALYSIS OF INORGANIC ACID, BASIC RADICALS, AND ESTIMATION OF BIOMOLECULES IN THE FLOWER EXTRACT OF BUTEA SUPERBA ROXB. - B, Seethalakshmi; K, Kavitha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Medicinal plants have different chemicals in their roots, stem, leaves, flowers, and fruits. In human history, medicinal plants play a vital role in the traditional medicine because of herbal plants have a great nutritive value, and some of them are also used in medicine. The efficacy of medicinal plants is mainly allied with their components such as secondary metabolites and inorganic acid, and basic radicals considered that prolonged intake can cause health problems if the heavy metals such as mercury, cadmium, and other impurities are the threshold concentrations. Methods: In the present study, the flower extract of Butea superba was analyzed for the inorganic acid and basic radicals and the estimation of total saponins, terpenoids, and alkaloids. The above protocols were done using standard methods. Results: The flower extract of B. superba revealed that the inorganic acid radicals such as chromate, phosphate, and sulfate and the basic radicals such as lead, arsenic, and ferrous showed that positive results. The percentage of total saponins, terpenoids, and alkaloids were compared in the following order, saponins<terpenoids<alkaloids as 4.181±0.017%<79.833±0.351%<107.823±0.105%, respectively. Conclusion: The present study revealed that the inorganic acid and basic elements of B. superba flower extract. The estimation of secondary metabolites such as total saponins, terpenoids, and alkaloids proved that the flower extract of B. superba is used to treat many diseases.